Management systems and performance frameworks for sustainability a road map for sustainably managed enterprises - James, Lowellyne (Routledge, 2018)
All organisations have a responsibility to ensure they have a minimum negative impact on the environment and act as a haven for human development that contributes to positive outcomes for society. But small businesses have limited resources with which to pursue sustainability initiatives and must focus on their core objectives in order to survive. Through an in-depth exploration of quality management theory, this book proposes a "Sustainability Management Framework" as a structure for a balanced approach to developing operations strategy for corporate social responsibility (CSR)Management Systems and Performance Frameworks for Sustainability explores the frameworks, accreditations and awards that small to medium sized enterprises (SMEs) can utilise to enhance their performance. In the firsthalf of the book, the author demonstrates how complementary techniques such as the Sustainability Performance Framework can help organisational leaders to develop, implement and optimise business strategy into discrete activities of value setting, management system and performance model selection, and target setting and evaluation, to the tactical deployment of sustainability and CSR. Meanwhile, the second half of the book focuses on real SME case studies to illustrate the use of the Sustainability Strategic Growth Model, Sustainability Management Framework and Sustainability Performance Framework to align strategy and policies with compliance obligations, United Nations Sustainable Development Goals and Millennium Development Goals.This key book is vital reading forundergraduate and postgraduate studentsof quality management, entrepreneurship and sustainability in business, executives of SMEs and sustainability policymakers